Intraspecific higher order interactions enhance ecological community stability - Akihiko Mougi (Scientific Reports)
Abstract Ecosystem stability is influenced by interspecific interactions, with recent research focusing on how third-party species modify these interactions. However, the impact of "intraspecific higher-order interactions," where the presence of one species affects intraspecific interactions within another species, on ecosystem stability has been less explored. This study addresses this gap by developing a mathematical model to investigate how such interactions influence stability. The analysis shows that when higher-order interactions increase intraspecific competition within another species, stability improves, especially in large, complex ecosystems. However, this effect is not observed if the interactions solely increase or decrease competition without a mixture of both. These findings highlight the importance of both positive and negative effects on intraspecific competition for enhancing stability in complex ecosystems. This emphasizes the need for further research on the role of higher-order interactions in shaping ecosystem stability, particularly in complex ecosystems.